Documentation of communication and receptive language skills in a case of Rett syndrome - Gómez Taibo, María Luisa; Paramos Alonso, Sara (Revista de Investigación en Logopedia, 2022)
Difficulties in producing verbal and motor responses in people with Rett Syndrome (RS) who need Augmentative and Alternative communication makes assessment difficult; therefore, is necessary to combine informal assessment methods and adaptations in formal instruments to obtain information on levels of competence. The aim of this study is to document the process of communication & linguistic skills’ assessment carried out with a girl with RS by combining assessment methods and making adaptations to standardized tests. Informal observations were conducted in natural settings; communication partners filled the Communication Matrix, and adaptations were made to the Peabody Picture Vocabulary test, the TSA of morpho-syntax development, and the Test of Aided Communication Performance, consisting of reducing the number of alternatives, presenting them in a layout accessible to eye gaze, and waiting extra time for the RS participant’s response. Results obtained through adaptations using gaze as the access method showed levels of mastery of pre-intentional communication and unconventional communication, along with emerging skills in conventional and symbolic communication for requesting and for social interaction, and an understanding of simple grammatical structures. The conclusion is that assessment must be tailored to the physical and speech limitations of individuals with Rett syndrome, so that hidden abilities can be uncovered, goals for intervention may be set based on their actual levels of competence to maximally support communication.